Clinical epidemiology of cardiovascular disease in advanced chronic kidney disease prior to dialysis to a tertiary care centre in Bangladesh (Bangladesh Journal of Medicine, 2024)
Background: Patients with advanced CKD stages exhibit a markedly elevated risk of cardiovascular disease. Patients with chronic kidney disease (CKD) exhibit an elevated cardiovascular risk manifesting as coronary artery disease, heart failure, arrhythmias, and sudden cardiac death .The main objective of this study was to observe the clinical epidemiology of cardiovascular disease in advanced stages of CKD prior to dialysis to a tertiary care centre in Bangladesh. Methods: This was a cross-sectional observational study on 150 cases of diagnosed advanced stages (4&5) of CKD patients in the indoor Department of Medicine of Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh from July 2022to January2023 for 6 months. Data was analyzed SPSS 25. Results: Out of the total group, 62.0% are male, 38.0% are female, and the average (mean) age of the entire group was 55.2 ±10.3. Patients are compared in terms of their relative percentages and the associated cardiovascular disease (CVD) risk, with the hypothesis that lower hemoglobin levels (